Environmental governance in China: Interactions between the state and "nonstate actors". (15th August 2018) - Guttman, Dan; Young, Oran; Jing, Yijia; Bramble, Barbara; Bu, Maoliang; Chen, Carmen; Furst, Kathinka; Hu, Tao; Li, Yifei; Logan, Kate; Liu, Lingxuan; Price, Lydia; et al.
Abstract: In the West, limited government capacity to solve environmental problems has triggered the rise of a variety of "nonstate actors" to supplement government efforts or provide alternative mechanisms for addressing environmental issues. How does this development - along with our efforts to understand it - map onto environmental governance processes in China? China's efforts to address environmental issues reflect institutionalized governance processes that differ from parallel western processes in ways that have major consequences for domestic environmental governance practices and the governance of China "going abroad." China's governance processes blur the distinction between the state and other actors; the "shadow of the state" is a major factor in all efforts to address environmental issues. The space occupied by nonstate actors in western systems is occupied by shiye danwei ("public service units"), she hui tuanti ("social associations") and e-platforms, all of which have close links to the state. Meanwhile, international NGOs and multinational corporations are also significant players in China. As a result, the mechanisms of influence that produce effects in China differ in important ways from mechanisms familiar from the western experience. This conclusion has far-reaching implications for those seeking to address global environmental concerns, given the importance of China's growing economy and burgeoning network of trade relationships. Highlights: "Nonstate actors" play increasing roles in global environmental governance. The western "non state actor" concept is inadequate to describe China developments. This article proposes a framework for their study in China. The article explains why this study is essential on multiple counts.